How to Think About International-World Affairs from Latin American Thought: An Analysis of the Theorization - Deves-Valdes, E (UNIV DO VALE DO RIO DOS SINOS, 2013)
This article is a bibliographical analysis of the publications on international-world affairs by Latin American authors from 2000 onwards. I intend to show that this bibliography is oriented to the elaboration of a Latin American theoretical approach. This topic was treated in relation to themes such as paradigms, schools of thought, ideal types and theories (structuralism, peripheral realism, autonomy, among others). The hypothesis I intend to prove is the existence of a reflection about the epistemological possibility of a Latin American theoretical approach and the discussion about the need for it and its potential contributions.